DAMPAK PENUTUPAN LOKALISASI PUGER KULON TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT PUGER KABUPATEN JEMBER - EKO SETIAWAN Eko (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2023)
Prostitution is a disease of society as old as human life itself cannot be eliminated because it always exists in every age. It is a classic problem because it needs serious government handling in overcoming the problem of prostitution. It is undeniable that it can increase the economic growth of the people around the localization. This research uses qualitative research methods. The data collection method uses observation, in-depth interviews and documentation. Data analysis using interactive models, including data collection, data reduction, data presentation. The results showed positive and negative views of the community about the existence of localization. The existence of localization will only cause bad impacts and harm people's lives. However, there are those who think that localization can be profitable from an economic point of view. The social impact of the existence of localization interferes with the mental development of children and decreases the level of religiosity. Meanwhile, the economic impact is felt by business actors who depend on their lives in localization areas complaining because income has decreased